Transparency, Credibility and Predictability of Monetary Policy under Inflation Targeting in South Africa. - Aron, J; Muellbauer, J (2007)
The adoption of inflation targeting in 2000 aimed to enhance the transparency and effectiveness of monetary policy in South Africa. Quantitative indexes reveal a strong rise in the transparency of monetary policy between 1994 and 2007. Inflation and interest rate expectations data, forward interest rate data and estimates of an interest rate policy rule, are used to explore the credibility and predictability of monetary policy since adopting inflation targeting. The evidence points to the new monetary policy framework being well-entrenched in financial markets’ expectations as early as 2001. Only small declines in interest rate forecast errors arise thereafter.